Prevalence of metabolic syndrome among staff in a Malaysian public university based on Harmonised, International Diabetes Federation and National Cholesterol Education Program Definitions - Heng, Kiang Soon; Abdul Rahman, Hejar; Abdul Aziz, Rushdan; Loh, Su Peng (Nutrition Society of Malaysia, 2013)
INTRODUCTION: Metabolic syndrome (MetSyn) as defined by the latest Harmonised definition and the agreement between the Harmonised definition and other definitions is poorly studied among Malaysians. This study was conducted to determine and compare the prevalence of MetSyn according to the Harmonised, International Diabetes Federation (IDF) and National Cholesterol Education Program (NCEP ATPIII) definitions among Malay staff of Universiti Putra Malaysia (UPM).